Constitutive expression of the UGA4 gene in Saccharomyces cerevisiae depends on two positive-acting proteins, Uga3p and Uga35p - Correa Garcia, Susana Raquel (2000)
The first specific precursor of porphyrin biosynthesis is delta-aminolevulinic acid. delta-Aminolevulinic acid enters Saccharomyces cerevisiae cells through the gamma-aminobutyric acid specific permease Uga4p. It was described that this permease is inducible by gamma-aminobutyric acid and its regulation involves several specific and pleiotropic transcriptional factors. However, some studies showed that under certain growth conditions the synthesis of Uga4p was not dependent on the presence of gamma-aminobutyric acid. To study the effect of the trans-acting factors Uga43p, Uga3p, Uga35p, Ure2p and Gln3p on the expression of UGA4, we measured gamma-aminobutyric acid and delta-aminolevulinic acid uptake in yeast mutant cells, lacking one of these regulatory factors, grown under different conditions. Experiments analyzing the UGA4 promoter using a fusion construction UGA4::lacZ were also carried out. The results show that the constitutive expression of the UGA4 gene found in cells under certain growth conditions depends on the presence of Uga3p and Uga35p. In contrast, Gln3p and Ure2p do not seem to have any effect on this constitutive mechanism.